Pendampingan Strategi UMKM di Era Digital Melalui Pencatatan Keuangan, Penghitungan Harga Pokok Produksi dan Manajemen Pemasaran untuk Dapat Naik Kelas: MSME Strategy Assistance in the Digital Era Through Financial Recording, Calculation of Cost of Production and Marketing Management to Get Upgrading - Supardi, Supardi; Sriyono, Sriyono; Hermawan, Sigit (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The success story of a PIA entrepreneur in Kejapanan Village, Gempol District, Pasuruan Regency. And became famous until he became one of the Pasuruan Icons. PIA Cake Entrepreneur RB Warurejo Gang Nangka, Kejapanan has been established for 11 years. The price of PIA RB being sold consists of several types of variants as follows: 1) PIA RB cakes with green bean, pineapple and strawberry variants costing Rp. 5000/box of 6 pia cakes. 2) Chocolate, Cheese and other PIA RB cakes for Rp. 7000/box of 6 pia cakes. The PIA RB production system that is implemented is: 1) based on orders or by order. 2) done conventionally. And 3) done with an open layout. The marketing strategies carried out: 1) conversational marketing is a marketing strategy that builds on conversations or conversations. 2) through marketplaces such as shopee, Tokopedia, and others. MSME Assistance Strategies Needed in the Digital Age Through Financial Records, Calculation of Cost of Production, and Improved Marketing Management. The PIA RB Cake Entrepreneur has a workforce of 13 people and is still carried out conventionally and assisted by several workers. The solution offered by this service is to provide MSME strategy training in the Digital Age by providing production management, financial management and marketing management training. The benefits obtained can educate PIA RB entrepreneurs in Warurejo Gang Nangka, Warurejo, Kejapanan, to be able to work according to standards, think creatively and innovatively and be able to apply operational management, financial management and marketing management properly.